Assessment of the bioactivity of bioinspired magnesium oxide nanoparticles from the Azadirachta indica extract - Al-Harbi, Laila M.; Ezzeldien, Mohammed; Elhenawy, Ahmed A.; Said, Alaa Hassan (Frontiers in Bioengineering and Biotechnology, 2024)
Azadirachta indica (neem) extract was used to biologically synthesize magnesium oxide nanoparticles. The synthesized NPs were characterized using XRD, TGA, TEM, SEM, FTIR, and Uv-vis spectroscopy. Antioxidant, anticancer, antibacterial, antidiabetic, and anti-inflammatory activities were performed for the synthesized MgO NPs and neem extract. The obtained results confirm the synthesis of spherical magnesium oxide nanoparticles with an average particle size of 23 nm by using XRD.The samples have good thermal stability with high stability in biological media. In comparison to neem extract and chemically synthesized magnesium oxide nanoparticles, bioinspired magnesium oxide nanoparticles showed considerable free radical scavenging activity with IC50= 69.03 µg/ml. In addition, it reflected high selectivity to Liver hepatic cancer cells with IC50= 94.85 µg/ml without inducing any damage to Human umbilical vein endothelial cells. The antibacterial activity of bioinspired magnesium oxide nanoparticles demonstrated comparable effectiveness in treating both gram-positive and gram-negative bacterial strains. Further, the produced bioinspired magnesium oxide nanoparticles possess a high percentage of inhibition for both α-amylase and α-glucosidase enzymes with IC50= 61. 53 and 50.6 µg/ml, respectively. Also, bioinspired magnesium oxide nanoparticles showed a higher denaturation inhibition percentage with IC50= 6.66 µg/ml, indicating its high antiinflammatory action. These enhanced abilities usher in a new bioinspired magnesium oxide nanoparticle bio-applications era. Consequently, further in vivo studies are needed to assess the kinetic properties of these nanoparticles.